Penggunaan Teknologi Dalam Inovasi Pendidikan - Hashim, Yusup (Penerbit Universiti Sains Malaysia, 1994)
This paper focusses on the types of educational innovations. particularly the use of educational technology in Malaysian schools and institutions of higher education. Various studies on the problems of implementation of educational technology innovations are discussed. Factors that determined the adoption and diffusion process according to Havelock (1971) are discussed with specific examples from Malaysian experience.